Expressão de receptores opióides (μ e κ), marcador de angiogênese, proliferação e morte celular no câncer de mama - Sousa, Alceu Machado de (2017)
Breast cancer represents a disease of great concern due to its high incidence and high mortality and is currently considered the second largest cause of death in the world. It is known that the prognosis of this tumor is directly related to its staging, with more advanced stages responsible for lower survival and impairment in the patient's quality of life, mainly due to pain complaints. Opioids are widely used to minimize pain at the oncology clinic. In the literature there are conflicting results regarding the use of opioid drugs and their action on tumor cells and the process of angiogenesis in the tumor micro-environment. Therefore, this study aimed to evaluate the expression of mu (μ), Kappa (κ) opioid receptors, correlating with prognostic factors such as markers of angiogenesis (VEGF), cell proliferation (Ki-67) and cell death (TUNEL) in Biopsies of tumors with T4 staging, with or without metastatic process, stratified for the Luminal A and Luminal B molecular subtype, diagnosed and operated at Haroldo Juaçaba Hospital (Ceará Cancer Institute) from 2011 to 2016. A total of 38 biopsy specimens from Luminal A and Luminal B breast cancer patients with T4 tumor size, with and without metastatic process, diagnosed, treated and operated at the abovementioned Hospital were included in the study. Demographic data and tumor characteristics, including the use of opioids and the presence of disease recurrence, were also a reason for evaluation and comparison. In addition, in the present study, the expression, by immunohistochemistry, of the μ and κ opioid markers, VEGF, Ki-67 and TUNEL in the breast biopsy samples by the Tissue Microarray (TMA) technique was evaluated. Our results demonstrated that: 1. It was found that there is a significant predominance of ki67 immunoblotting in lymph nodes in patients who used opioids when compared to patients who did not use opioids in the clinical follow-up (p = 0.011); 2. It was evidenced that patients of the Luminal A molecular subtype present a significant increase in the chances of presenting a 51-75% T cell count in the tumor when compared to patients defined as Luminal B subtype (p = 0.020, OR = 21.000; CI = 1,613-273,340); 3. It was possible to show that patients with T4 staging who presented recurrence (7.2 ± 3.7) demonstrated a decrease in the histoscore expression of the Opioid κ in the lymph node location when related to the patients who did not present clinical evolution associated with relapse (10.8 ± 2.2) (p = 0.033) and 4. The correlation analyzes between the opioid μ and κ markers, VEGF, Ki-67 and TUNEL demonstrate that these findings probably act on the same cascade of events in the CA of T4 stage breast. Our study demonstrated that the use of opioids is directly associated with the increase in ki-67 expression and the prevalence of relapses, which showed lower expression for the opioid kappa receptor. In addition, there was no significant difference in the biological behavior of luminal A and luminal B tumors and the immunoexpression of opioid receptors were independent of angiogenesis receptors. In summary, in luminal A and luminal B tumors the use of opioids is directly associated with a worse prognosis, due to reduction of opioid kappa receptor expression.